Perbandingan flexural strength resin semen self adhesive dan resin semen adhesive dual cure - Salma, Khansa; Handojo, James; Hapsari Andayani, Lia (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Resin cement is a cement luting material that is widely used in the field of dentistry because it has superior mechanical and physical properties compared to other luting materials. The composition of resin cement greatly affect the physical and mechanical properties of the resin cement. Dual cure self-adhesive resin cement and dual cure adhesive resin cement are in fact only different based on the adhesive material. However, both materials have several different compositions that can affect the mechanical properties, one of which is flexural strength. Objectives: This study aimed to determine the flexural strength of self-adhesive dual cure and adhesive dual cure resin cement materials. Methode: This study is an experimental research that was performed at the Dental Material and Testing Centre of Research and Education (DMT Core) Laboratory, Faculty of Dentistry, Universitas Trisakti, Jakarta. The object of the study was self-adhesive dual cure and adhesive dual cure resin cement materials. The resin cement was put into the preparation tube and then attached to the automix tip. Inject the samples on a rectangular mould with dimensions of 25 mm long, 2 mm wide, and 2 mm high which can then be light cured. The sample was made as many as 8 samples. The flexural strength test can be carried out using a Universal Testing Machine (UTM) at a speed of 0.75mm/min. The resulting data was tested for normality with Saphiro Wilk and Independent T test. Conclusion: Dual cure self-adhesive resin cement has a higher average flexural strength value than and dual cure adhesive resin cement.